“Gold Standards,” Plurality and Monocultures: The Need for Diversity in Psychotherapy - Leichsenring, Falk; Abbass, Allan; Hilsenroth, Mark J.; Luyten, Patrick; Munder, Thomas; Rabung, Sven; Steinert, Christiane (Frontiers in Psychiatry, 2018)
For psychotherapy of mental disorders, presently several approaches are available, such as interpersonal, humanistic systemic psychodynamic or cognitive behavior therapy (CBT) Pointing to the available evidence, proponents of CBT claim that CBT is the gold standard . Some authors even argue for an integrated CBT-based form of psychotherapy as the only form of psychotherapy. CBT undoubtedly has its strengths and CBT researchers have to be credited for developing and testing treatments for many mental disorders. A critical review, however, shows that the available evidence for the theoretical foundations of CBT, assumed mechanisms of change, quality of studies and efficacy is not as robust as some researchers claim. Most important, there is no consistent evidence that CBT is more efficacious than other evidence-based approaches. These findings do not justify regarding CBT as the gold standard psychotherapy. They even provide less justification for the idea that the future of psychotherapy lies in one integrated CBT-based form of psychotherapy as the only type of psychotherapy. For the different psychotherapeutic approaches a growing body of evidence is available. These approaches have their strengths because of differences in their respective focus on interpersonal relationships, affects, cognitions, systemic perspectives, experiential or unconscious processes. Different approaches may be suitable to different patients and therapists. As generally assumed progress in research results from openness to new ideas and learning from diverse perspectives. Thus, different forms of evidence-based psychotherapy are required. Plurality is the future of psychotherapy, not a uniform “one fits all" approach.